2019
DOI: 10.14814/phy2.14109
|View full text |Cite
|
Sign up to set email alerts
|

Muscle assessment using multi‐frequency bioimpedance in a healthy Danish population aged 20–69 years: a powerful non‐invasive tool in sports and in the clinic

Abstract: The condition of active muscles determines an individual′s ability to carry out daily activities and has implications for an athlete′s performance. Multi‐frequency bioimpedance (mf BIA ) is a non‐invasive, well‐known, validated, and much used method to assess muscle condition. However, it is rarely used to its full potential. Our aim was to apply mf BIA fully in the assessment of an adult healthy population, to compare muscle condition in different functional reste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…An earlier study by this group has already demonstrated, in a larger healthy adult population spanning 20–69 years in both males and females, that mfBIA parameters differ with gender (Bartels et al, 2019 ). For all the muscles measured in this study, we found, as expected, the gender difference for mfBIA parameters.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…An earlier study by this group has already demonstrated, in a larger healthy adult population spanning 20–69 years in both males and females, that mfBIA parameters differ with gender (Bartels et al, 2019 ). For all the muscles measured in this study, we found, as expected, the gender difference for mfBIA parameters.…”
Section: Discussionmentioning
confidence: 90%
“…For all the muscles measured in this study, we found, as expected, the gender difference for mfBIA parameters. Likewise, this technique is not only non‐invasive, but it is also fast and has been shown over the years to be reliable and repeatable, and can be recommended for use in the clinic (Bartels et al, 2015 ; Bartels et al, 2019 ; Harrison et al, 2015 ; Nescolarde et al, 2013 ; Nescolarde et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Muscle activity can be evaluated by e.g., electromyography and acoustic myography (AMG), the latter also called mechanomyography ( 8 ). While muscle mass and tone may be estimated by simple palpation, objective information about mass and muscular health can be obtained from multi-frequency bio-impedance or ultrasound ( 9 , 10 ). Magnetic resonance imaging (MRI) and computed tomography (CT) are other imaging methods available to evaluate muscles ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%